A linguist’s reminiscences to identification theory: epistolary of Panteleimon Kulish. Article 1 - Shevchenko, Larysa` (Current issues of Ukrainian linguistics: theory and practice, 2019)
In E. Erickson’s theory of identification the article analyses the epistolary of Panteleimon Kulish – an outstanding Ukrainian culturologist, publisher, writer and translator. The author states that E. Erickson’s theory created the intellectual matrix of a person’s development analysis in the system of psychosocial conditions and circumstances. The scholar studies E. Erickson’s main postulate, namely the correlation of a personality with psychosocial identity. Therefore, a personality can be interpreted in the integrity of various motivations, traditions, values, ideals and their social roles. The author explores the influence of cultural and historical factors on a person’s psycho-emotional and creative structure. The theory of evolution is considered, which, according to E. Erickson, defines eight universal stages of human development. The scholar investigates the principles of development stages, i.e. a) progressive development of a person, which is ready to evolve in the direction of further growth, expansion of the perceived outlook and possibilities of social interaction; b) the development of a person’s social and creative capabilities in coordination with changes in society, when society promotes preservation of interaction trends. The major problem in the analysis of P. Kulish’s creative person is the problem of ethnic identification. The article explores the criteria of P. Kulish’s ethnic identification: existential choice, ways of self-realization, achievement of internal freedom, solving individual-psychological problems of belonging to a certain social strata, realization of a person’s powerful intentions in the national language.